Design Principles and Applications of Selective Lanthanide-Based Receptors for Inorganic Phosphate - Pierre, Valérie C.; Wilharm, Randall K. (Frontiers in Chemistry, 2022)
Phosphate is an anion of both environmental and medical significance. The increase in phosphate levels in surface waters due primarily to run-offs from fertilized agricultural fields causes widespread eutrophication and increasingly large dead-zones. Hyperphosphatemia, a condition in which blood phosphate levels are elevated, is a primary cause of increased mortality and morbidity in chronic or advanced kidney disease. Resolving both of these issues require, in part, new technology that could selectively sequester phosphate in water at neutral pH. The high hydration energy of phosphate, which prevents organic receptors from functioning in water with sufficient affinity, can be overcome via coordination to a hard metal ion. The hardness, oxophilicity and lability of lanthanide ions make them excellent candidates for the design of high affinity phosphate receptors. In this perspective, we discuss how the principles of lanthanide coordination chemistry can be exploited to design sensitive and selective receptors for phosphate. Unlike many supramolecular systems, these hosts do not recognize their anionic guests via directed electrostatic and hydrogen bonding interactions. Instead, the selectivity of our fluxional receptors is governed entirely by acid-base chemistry and electrostatic forces. Parameters that affect the affinity and selectivity of the receptors include the basicities of the coordinating ligand and of the targeted anion, the acidity of the lanthanide ion, and the geometry of the ligand. Uniquely, their affinity for phosphate can be readily tuned by orders of magnitude either by peripheral interactions or by the lanthanide ion itself without affecting their exquisite selectivity over competing anionse.